Comparison of Various Control Techniques for Clove Stem Borer (Nothopeus hemipterus) in Samigaluh, Kulon Progo - Sidiq, Muhamad Fajar; Wisnubroto, Muhammad Parikesit; Handru, Alan; Avianto, Yovi; Putri, Diyona (Jurusan Budidaya Perkebunan, 2025)
The clove stem borer (Nothopeus hemipterus) is a major pest causing significant economic losses in clove cultivation. In Samigaluh, most farmers rely on chemical pesticides for control. However, essential oils and entomopathogenic fungi offer safer and more sustainable alternatives. This study aimed to evaluate their effectiveness and determine the most suitable control method. The research was conducted in Kayugedhe Hamlet, Samigaluh, Kulon Progo, Yogyakarta, from April to September 2022. A randomized completely block design was used with different pest control treatments, including chemical pesticides (fipronil, acephate, and profenofos), botanical pesticides (10% neem oil and 10% citronella oil), biological pesticides (Beauveria bassiana at 1 × 10⁸ CFU/mL), and a control. The pesticides were applied using a hydraulic pump and a wax-sealing method on larval entry holes. Larval mortality was recorded weekly for four weeks. The results showed that the application of entomopathogenic fungi (Beauveria bassiana) and citronella oil led to larval mortality rates of 78% and 75%, respectively, which were comparable to the effectiveness of fipronil (80%) and acephate (81%). In contrast, N. hemipterus larvae exhibited lower susceptibility to profenofos, with a mortality rate of only 47%, suggesting potential resistance. These findings indicate that B. bassiana and citronella oil extract could serve as effective and environmentally friendly alternatives for controlling the clove stem borer.